Causal mechanisms in the clinical course and treatment of back pain. Issue 6 (December 2016) - Lee, H.; Mansell, G.; McAuley, J.H.; Kamper, S.J.; Hübscher, M.; Moseley, G.L.; Wolfenden, L.; Hodder, R.K.; Williams, C.M.
Abstract: In recent years, there has been increasing interest in studying causal mechanisms in the development and treatment of back pain. The aim of this article is to provide an overview of our current understanding of causal mechanisms in the field. In the first section, we introduce key concepts and terminology. In the second section, we provide a brief synopsis of systematic reviews of mechanism studies relevant to the clinical course and treatment of back pain. In the third section, we reflect on the findings of our review to explain how understanding causal mechanisms can inform clinical practice and the implementation of best practice. In the final sections, we introduce contemporary methodological advances, highlight the key assumptions of these methods, and discuss future directions to advance the quality of mechanism-related studies in the back pain field.